2022
DOI: 10.3389/fphys.2022.1073307
|View full text |Cite
|
Sign up to set email alerts
|

Critical periods in Drosophila neural network development: Importance to network tuning and therapeutic potential

Abstract: Critical periods are phases of heightened plasticity that occur during the development of neural networks. Beginning with pioneering work of Hubel and Wiesel, which identified a critical period for the formation of ocular dominance in mammalian visual network connectivity, critical periods have been identified for many circuits, both sensory and motor, and across phyla, suggesting a universal phenomenon. However, a key unanswered question remains why these forms of plasticity are restricted to specific develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…A large body of work, mostly performed in rodents, has shown that maturation of neural circuits is dependent on an interplay between excitatory and inhibitory activity, particularly during developmental CPs (Wong-Riley, 2021; Hensch, 2005; Hensch and Bilimoria, 2012; Gervain et al ., 2013). CPs often reflect a change from spontaneous to patterned activity within neural networks (Coulson et al ., 2022). Early spontaneous activity that occurs prior to CP opening is predominantly excitatory and notably includes excitatory GABAergic signalling (Ben-Ari, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of work, mostly performed in rodents, has shown that maturation of neural circuits is dependent on an interplay between excitatory and inhibitory activity, particularly during developmental CPs (Wong-Riley, 2021; Hensch, 2005; Hensch and Bilimoria, 2012; Gervain et al ., 2013). CPs often reflect a change from spontaneous to patterned activity within neural networks (Coulson et al ., 2022). Early spontaneous activity that occurs prior to CP opening is predominantly excitatory and notably includes excitatory GABAergic signalling (Ben-Ari, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…How neurons measure levels of activity during the CP remains under active investigation (Zeng et al ., 2021; Carreira-Rosario et al ., 2021; Giachello et al ., 2021; Coulson et al ., 2022; Reh et al ., 2020; Peters and Naneix, 2022; Gibel-Russo, Benacom and Di Nardo, 2022). The second messenger calcium is likely to be involved, as calcium signalling is central to activity-regulated plasticity during nervous system development, including adjustment to changing internal and external environments, as well as learning and memory (Spitzer, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This temporally-restricted circuit remodeling is absolutely essential, as the last chance for significant renovation of genetically-determined brain synaptic connectivity to match the unpredictable, variable environmental input 4 . As in mammals, Drosophila critical periods open with sensory experience 5 7 , close to remodeling after a brief window 6 , 8 , 9 , and are only transiently reversible during this tightly restricted interval 10 12 . A classic critical period happens in the first few days after Drosophila eclosion, when striking brain olfactory circuit antennal lobe synaptic glomeruli remodeling occurs in response to early sensory input 5 .…”
Section: Introductionmentioning
confidence: 97%
“…Manipulations during critical periods (CPs) often drive permanent change that becomes locked in. Similar manipulations during sensitive periods (SPs) can be equally profound but, differentially, can be modified following period closure (14). First conceptualized in the 1960s (5), CPs are developmental windows during which changes in neural activity support both anatomical and functional tuning of neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…First conceptualized in the 1960s (5), CPs are developmental windows during which changes in neural activity support both anatomical and functional tuning of neural networks. This includes the possible encoding of homeostatic “set points” that ensure appropriate activity levels in both neurons and neural networks (1, 4, 6–8). Previous work from our group has identified a CP in the Drosophila embryo, during 17-19 hours after egg laying (AEL), during which activity-manipulation is sufficient to permanently change the stability of the locomotor network (6, 9).…”
Section: Introductionmentioning
confidence: 99%